Sea level change in the Malaysian seas from multi-satellite altimeter data - Md. Din, Ami Hassan (2009)
Seas from satellite altimetry data of the Topex, Jason-1, ERS-1, ERS-2 and Envisat missions. During the past two decades, satellite altimeter has provided its capability in measuring the global mean of sea level with precision better than 1 mm/year. Sea level data retrieval and reduction were carried out using Radar Altimeter Database System (RADS). In RADS data processing, the recently updated environmental and geophysical corrections were applied. Sixth 1° × 1° areas were chosen for the altimeter data comparison and to find the best ocean tide model for Malaysian Seas, where the altimeter tracks are nearby to tide gauge locations. Similarity in the pattern of sea level variations indicated good agreements between tide gauge data and altimeter data using FES2004 ocean tide model. It also showed that the altimeter data can be used to investigate sea level rise for Malaysian Seas. Here, sea level variations for four areas in the Malaysian Seas have been investigated using 15 years of altimeter data. The altimeter sea level time series revealed that since 1993, the mean sea level in Malaysian Seas has been rising at a rate of between 1.42 – 4.08 mm/year. This information is important to study alternative energy extraction and environmental issues related to flood investigations and global warming.